2010
DOI: 10.1111/j.1468-2273.2009.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Model of Funding for Academic Research in Nigerian Universities

Abstract: Funding of academic research in Nigerian universities by Government (5 per cent recurrent grants) is a policy dictated by the National Universities Commission (NUC) as the central body for allocating research funds.This research fund, little as it is, is irregular and inadequate and to make it worse isdifficult to access. These aforementioned factors have contributed to the decline in research activity as a means of attaining sustainable development in Nigeria. Thus, this article proposes a dual support system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…1 Unlike most developed countries where 1.5%–3.0% of the gross domestic product (GDP) is spent on research, available data showed that the total yearly budgetary allocation to research in Nigeria is about 0.3% of the GDP, far below the National Science Policy which recommends 5%. 8 Research funding, to a large extent, determines the quality of research output. 8 Therefore, poor funding might have accounted for a restriction in the scope of researches to those which could be achieved with low-to-medium budgets and consequently lead to its limited contribution to new knowledge or impact.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unlike most developed countries where 1.5%–3.0% of the gross domestic product (GDP) is spent on research, available data showed that the total yearly budgetary allocation to research in Nigeria is about 0.3% of the GDP, far below the National Science Policy which recommends 5%. 8 Research funding, to a large extent, determines the quality of research output. 8 Therefore, poor funding might have accounted for a restriction in the scope of researches to those which could be achieved with low-to-medium budgets and consequently lead to its limited contribution to new knowledge or impact.…”
Section: Discussionmentioning
confidence: 99%
“…[19] In trying to address the burden of proper funding of the educational sector, the federal government through the Minister of education had call on society to participate in the provision of university education with the government. [20] Nigeria is the most populous country in Africa with an estimated population of over 180 million people.…”
Section: Evolution Of Nursing In Nigeriamentioning
confidence: 99%
“…The effects of this funding problem could have resulted to some of Obonya's(2002) earlier observations alluding to deterioration of physical facilities; internal and external brain drain among the intellectual class; and overstretching of teaching, research and managerial capacities in Nigerian University system. In relation to the University's mandate on research for instance, Olayiwola (2010) claimed that since most research input and equipment are imported, the purchasing power of the Naira has been weakening as a result of devaluation of currency caused by the poor state of the economy. Most of the input in the form of books, journals, and laboratory equipment could not be sustained for research activities (Olayiwola, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In relation to the University's mandate on research for instance, Olayiwola (2010) claimed that since most research input and equipment are imported, the purchasing power of the Naira has been weakening as a result of devaluation of currency caused by the poor state of the economy. Most of the input in the form of books, journals, and laboratory equipment could not be sustained for research activities (Olayiwola, 2010). As a result of these daunting teaching and research situations, Universities administrators have consistently identified funding issues as a critical challenge in discharging their functions effectively (Shina, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%